(untitled) (Research, Society and Development, 2022)
The objective of this study is to report the case of a female dog with hysterocele gravidarum associated with driaphragmatic hernia. The animal presented clinical signs of dyspnea, tachypnea, muffled cardiac auscultation, presence of greenish secretion in the vulva and moderate pain on abdominal palpation. An ultrasound examination was performed based on the clinical suspicion of dystocic delivery, and the presence of two viable fetuses was confirmed. However, given the animal’s history, worsening and severity of the clinical condition, the animal was immediately referred for a surgical procedure for cesarean section. After accessing the abdominal cavity and attempting to retract the uterine horns, exposure was difficult, and it was necessary to increase the incision in a cranial direction. Thus, the presence of diaphragmatic rupture with part of the intestinal loops, right kidney and gravid uterus in the thoracic cavity was evidenced. During the procedure, the patient had a cardiorespiratory arrest and died. Thus, necropsy was chosen, which revealed diaphragmatic hernia, dystocic delivery and pulmonary atelectasis with consequent respiratory failure. It is concluded that the surgical correction of diaphragmatic hernias on an emergency basis is of paramount importance and, in cases where there is concomitant pregnancy, the severity of the effects makes the prognosis bad.